Testing the Impact of a Planning Policy Based on New Urbanist Planning Principles on Residents' Sense of Community and Mental Health in Perth, Western Australia. Issue 3 (April 2020) - Hooper, Paula; Foster, Sarah; Knuiman, Matthew; Giles-Corti, Billie
There is growing concern that the built forms resulting from conventional suburban design may be adversely affecting the social well-being, sense of community, and psychological health of its residents. This study tested the premise that suburban neighborhood developments ( n = 36) designed in accordance with a New Urbanist inspired planning policy in Perth, Western Australia, improved residents' ( n = 644) sense of community and mental health. Findings revealed that with each 10% increase in policy compliance, residents odds of experiencing high sense of community increased by 21% ( OR = 1.21, 95% CI = [1.04, 1.41]) and low psychological distress increased by 14% ( OR = 1.14, 95% CI = [1.01, 1.28]). These results add empirical input to the debate surrounding the rhetoric and purported social goals and benefits of the New Urbanism, indicating that implementation of its neo-traditionalist neighborhood design principles may help create the conditions for positive neighborhood sense of community and mental health.